2011
DOI: 10.1136/ard.2010.138883
|View full text |Cite
|
Sign up to set email alerts
|

ASDAS, BASDAI and different treatment responses and their relation to biomarkers of inflammation, cartilage and bone turnover in patients with axial spondyloarthritis treated with TNF  inhibitors

Abstract: Levels and changes of 10 biomarkers in patients with axial spondyloarthritis during anti-TNFα therapy were documented. Construct validity and responsiveness of IL-6, VEGF, MMP-3, total aggrecan and osteocalcin were demonstrated. ASDAS was more associated with these biomarkers than BASDAI, and may better reflect the inflammatory disease processes. ClinicalTrials.gov identifier NCT00133315.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
83
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 27 publications
13
83
2
4
Order By: Relevance
“…The present authors' evaluation has demonstrated significantly lower serum VEGF levels in patients treated with TNFα inhibitors versus the untreated patients. These data are in accordance with the data of other authors in whose studies the administration of TNFα inhibitors resulted in a decrease in the VEGF level (16,18,19,20,21). For the time being it is not clear whether TNFα inhibitors influence radiographic progression in patients with AS.…”
Section: Discussionsupporting
confidence: 80%
“…The present authors' evaluation has demonstrated significantly lower serum VEGF levels in patients treated with TNFα inhibitors versus the untreated patients. These data are in accordance with the data of other authors in whose studies the administration of TNFα inhibitors resulted in a decrease in the VEGF level (16,18,19,20,21). For the time being it is not clear whether TNFα inhibitors influence radiographic progression in patients with AS.…”
Section: Discussionsupporting
confidence: 80%
“…One other limitation of this study was that we did not use the more sensitive index Ankylosing Spondylitis Disease Activity Score. 21 BASDAI is an established, reliable and valid disease activity measure in axSpA, but has been shown to be less sensitive to change in disease activity than Ankylosing Spondylitis Disease Activity Score in some studies. However, the fact that we were still able to detect significant associations between 25(OH)D and the Bath indices is a strength of the study.…”
Section: Discussionmentioning
confidence: 99%
“…While the ASDAS includes the categories of spinal pain, peripheral joint pain, morning stiffness, the patient's global assessment of disease activity, and laboratory parameters, [21][22][23] it does not include fatigue and local tenderness. The ASDAS-ESR levels of the female patients in this study were significantly higher than those of the male patients, but the ASDAS-CRP levels for both genders were similar.…”
Section: Discussionmentioning
confidence: 99%